Review of the genus Beckhoplia Dombrow, 2005 with the description of fifteen new species from South Africa and observations on its biogeography (Coleoptera: Scarabaeidae: Melolonthinae: Hopliini) - Dombrow, Holger E.; Colville, Jonathan F. (Zootaxa, 2020)
Fifteen years after establishing the genus Beckhoplia Dombrow, 2005 a large amount of new material collected has warranted a critical review of the established species and a revision of the genus. From this process, we describe fifteen new species from the Northern Cape Province and Western Cape Province of the Republic of South Africa: Beckhoplia bicolor Dombrow, new species, B. caliginosa Dombrow, new species, B. castanea Dombrow, new species, B. dolichiocnemis Dombrow, new species, B. elkeae Dombrow, new species, B. fusca Dombrow, new species, B. gifbergensis Dombrow, new species, B. nigra Dombrow, new species, B. nigrofasciata Dombrow, new species, B. nigrosetosa Dombrow, new species, B. pallidibrunnea Dombrow, new species, B. pulchra Dombrow, new species, B. pumilla Dombrow, new species, B. setosa Dombrow, new species and B. suturalis Dombrow, new species. Two cryptic species complexes within the species B. colvillei Dombrow, 2005 and B. occidentalis Dombrow, 2005 were detected. A revised key of the genus and observations about its biogeography are given. Important details of the morphological characters of the body and the parameres of the species are illustrated and their distributions are mapped. We also provide habitat and host plant information.